Priority Strategy for Mangrove Ecotourism Development at Budo Tourism Village - Luturkey, Maureen Fenesya; Paruntu, Carolus Paulus; Rumengan, Antonius Petrus; Ompi, Medy; Sumilat, Deiske Adeleine; Manembu, Indri Shelovita (Jurnal Ilmiah Platax, 2025)
This study was conducted for three months, starting from March to June 2024. The research method used was a qualitative descriptive method with a survey technique.  Data collection was carried out by collecting primary data and secondary data.  Data analysis to formulate priority strategies for developing mangrove ecotourism at Budo Tourism Village using SWOT analysis (strength, weakness, opportunity, threat) and strategy choice analysis to obtain key success factors (priority strategies). The results of this research obtained 7 (seven) priority strategies that can be used by stakeholders, especially BUMDES managers in Budo Village for the development of sustainable mangrove ecotourism. To create a public policy, it is recommended to the Budo Village government, especially the BUMDES manager, to pay attention and consider academic studies from the Faculty of Fisheries and Marine Sciences, UNSRAT, in the form of 7 (seven) key success factors or priority strategies. Keywords: key success factors, mangrove ecotourism, SWOT, strategic choice analysis   Abstrak   Riset ini dilaksanakan di kawasan ekowisata mangrove Desa Wisata Budo dan berlangsung selama 3 bulan, dimulai dari bulan Maret sampai Juni 2024.  Metode riset yang digunakan yaitu metode deskriptif kualitatif dengan teknik survei.  Pengumpulan data dilakukan dengan mengumpulkan data primer dan data sekunder.  Analisis data untuk merumuskan strategi pengembangan ekowisata mangrove Desa Wisata Budo menggunakan analisis SWOT (strength, weakness, opportunity, threat) dan analisis pilihan strategi untuk memperoleh faktor-faktor kunci keberhasilan (strategi prioritas). Hasil penelitian ini memperoleh 7 (tujuh) urutan strategi prioritas yang dapat digunakan oleh stakeholders, khususnya pengelola BUMDES Desa Budo untuk pengembangan ekowisata mangrove yang berkelanjutan. Dalam rangka membuat suatu kebijakan publik direkomendasikan kepada pemerintah Desa Budo, khususnya pengelola BUMDES untuk memperhatikan dan mempertimbangkan kajian akademik dari Fakultas Perikanan dan Ilmu Kelautan Unsrat berupa 7 (tujuh) faktor-faktor kunci keberhasilan atau strategi prioritas tersebut. Kata kunci: Analisis pilihan strategi, ekowisata mangrove, faktor-faktor kunci keberhasilan, SWOT